Evaluation of some physical parameters of persea americana in post-harvest measurement equipment - Cartagena Cutipa, Raul (2020)
In order to evaluate the post-harvest behavior of climacteric fruits, an experimental team was constructed to determine the intensity of respiratory rate in parts per million (ppm) of carbon dioxide (CO2) per unit of mass and time, for which purpose they were used : a K-33ICB sensor for CO2 measurement; Thomas 2000DV / 0,5 / E / LC air pump; a glass water trap with a diameter of 2.5 cm and a useful length of 6 cm; a 0.22 μm hydrophobic filter; a 150 μm particle filter; a breathing chamber with a volume of 5.0 x10-3 m3 constructed of glass with two tabulations for gas exchange and latex ducts. The Gaslab ® software was used to acquire data. In order to evaluate the equipment, Hass avocado fruits (Persea americana) were selected in the degree of physiological maturity with 8.26% of oil, then conditioned in the breathing chamber with an initial weight of one kilogram, then sealed hermetically to put into operation the equipment to record the respiratory rate during 24 days, at the end of the period, the fruit entered the climacteric process and the commercial maturity was determined with an oil content of 16.06%. The behavior of the respiratory rate of Hass avocado was typical of a climacteric fruit, presenting the climacteric peak on day 20 with 244 x 103 ppm / Kg. H. Physiological weight loss and firmness showed a decreasing behavior during the stage postharvest of the fruits, while the highest concentration of oil, was presented at 24 days postharvest, stage that coincided with the ripeness of consumption